Exploring the Issues of Social Inclusion in Queer Identities (Prithvi Academic Journal, 2019)
This is a qualitative study to explore the issues and status of social inclusion of queer identities i.e. lesbian, gay, bisexual, and transgender (LGBT). For this purpose, using the purposive technique, ten samples from Kathmandu and Pokhara were taken for interview along with a participatory observation. The generated data were presented in paraphrasing, verbatim, and case study form. The secondary data were reflexively embedded throughout the analysis. Confidentiality and cultural safety were maintained through the use of pseudo name in the study. The theory of recognition and the queer theory were used to make a discussion more trustworthy. The empirical data show that gender identity, relationships; social exclusion; effects of consumerism; school enrolment, and environment; employment, rental discrimination; polysexuality; sexual violence; and legalization of same-sex marriage or partnership were surfaced as the major issues of LGBT in Nepal. The empirical data also show that different people have different levels of exclusion. The identity issue against relationship is found a major threat for their inclusion. However, they were less worried about their own identity than their social relationships. Hence, they were compelled to maintain double standard identities because of the fear of relationship breakup. In this context, some steps are needed to be initiated for their inclusion, such as making gender and sexuality responsive policies and laws; institutionalizing collective identity; evading genderism, stereotyped stigma and superstitions; incorporating indigenous moralities and wisdom; improving heteropatriarchal norms; providing opportunity and environment of education; and making sexuality and LGBT friendly school curriculum and environment.